The curious incident of long COVID symptoms, from an imaginary condition to a recognised syndrome: a "small victory". Issue 6 (30th June 2022) - Di Mattei, Valentina E.; Perego, Gaia; Milano, Francesca; Hill, Thomas Eric; Harari, Sergio Alfonso
Over the past 2 years, the scientific community has acquired a better understanding about coronavirus disease 2019 (COVID-19) as an acute disease, but there is still much to learn, especially when considering the chronic aspects of this illness. In the early stages of the pandemic, healthcare workers focused on acute COVID-19 symptoms, often overlooking its long-term and chronic implications. In October 2021, the World Health Organization recognised these long-term complications as long COVID syndrome, which probably affected more than 62% of patients [1]. Patients with long COVID syndrome experienced the fear of living forever with those symptoms, arising from the lack of medical information on this issue [2], combined with the feeling of being ignored and disbelieved. Several patients felt they did not have access to appropriate healthcare, as they perceived that healthcare workers disregarded their symptoms and judged them as unreal, often considering them secondary to psychiatric issues [3]. In the early stages of the pandemic, patients with a post-COVID condition felt ignored and disbelieved by their doctors and relatives. Given the importance of the doctor–patient relationship in post-COVID management, we recommend "relationship-based care". https://bit.ly/3vQ9RO1